Multiple Haemangiomas, Diaphragmatic Eventration and Beckwith-Wiedemann Syndrome: An Unusual Association - Francisco, T (2016)
A 6-month-old girl with Beckwith-Wiedemann syndrome, multiple haemangiomas (axillary, laryngeal, pulmonary and hepatic) and diaphragmatic eventration was reported. All tumours responded to treatment with propranolol. The surgical correction of diaphragmatic eventration was crucial to a better outcome.